2021
DOI: 10.1002/jnr.24993
|View full text |Cite
|
Sign up to set email alerts
|

Input and output organization of the mesodiencephalic junction for cerebro‐cerebellar communication

Abstract: Cerebro-cerebellar communication is organized in multiple reciprocal loops. The information route from the cerebellum to the cerebral cortex (CC) includes either a direct connection from the cerebellar nuclei (CN) onto various subnuclei of the thalamus (Amino et al., 2001;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 126 publications
0
14
0
Order By: Relevance
“…These data indicate that the adaptive changes in the salience of inputs originate upstream of PCs. As the IO, from where the CFs originate, comprises a mixture of ascending excitatory inputs from sensory sources, descending excitatory inputs from cerebral cortical activity mediated via the mesodiencephalic junction, and inhibitory feedback from the cerebellar or vestibular nuclei (Bosman et al, 2011;Wang et al, 2021) (Figure 1A), it will be interesting to study this reconfiguration.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…These data indicate that the adaptive changes in the salience of inputs originate upstream of PCs. As the IO, from where the CFs originate, comprises a mixture of ascending excitatory inputs from sensory sources, descending excitatory inputs from cerebral cortical activity mediated via the mesodiencephalic junction, and inhibitory feedback from the cerebellar or vestibular nuclei (Bosman et al, 2011;Wang et al, 2021) (Figure 1A), it will be interesting to study this reconfiguration.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Instead, retrograde tracing from the bPN produced labeling in the caudal part of the MDJ, which we confirmed to be a source of GABAergic inputs to bPN neurons. The MDJ is a region located in the tegmentum that receives prominent inputs from neocortex and richly innervates the inferior olive with glutamatergic afferents ( De Zeeuw et al., 1998 ; Kubo et al., 2018 ; Wang et al., 2022 ). In a functional study, it was suggested that the inhibition of bPN neurons could be induced via a polysynaptic pathway from motor cortex ( Guo et al., 2021 ), and inhibition in bPN neurons has been observed in vitro after the stimulation of the cerebral peduncle and the tegmentum ( Möck et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the direct cerebellar-olivary projections there are other di-synaptic connections between cerebellar nuclei and inferior olive that could mediate the return of the cerebellar output to the cerebellar cortex via climbing fiber activity. Brain structures such as the meso-diencephalic junction and superior colliculus are known to receive inputs from cerebellar nuclei and excite inferior olivary nuclei [ 23 , 63 ]. The presence of these parallel recurrent pathways makes the olivocerebellar system a particularly suitable neuronal substrate for sustaining recurrent activity.…”
Section: Discussionmentioning
confidence: 99%